2016
DOI: 10.1002/lary.25996
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale of a prospective, multi-institutional registry for patients with sinonasal malignancy

Abstract: 2C Laryngoscope, 126:1977-1980, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…This investigation of a rare disease was completed using a prospective, multi-institutional approach. 14 Rare diseases are often difficult to study, with challenges stemming from small sample sizes, need for alternatives to randomized trial design, and limited resources, including funding. 19 Studies evaluating SNM treatment outcomes are further challenged by tumor diversity and evolving treatment paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation of a rare disease was completed using a prospective, multi-institutional approach. 14 Rare diseases are often difficult to study, with challenges stemming from small sample sizes, need for alternatives to randomized trial design, and limited resources, including funding. 19 Studies evaluating SNM treatment outcomes are further challenged by tumor diversity and evolving treatment paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors in literature conclude similarly that prospective multicentric studies are needed to reach higher patient numbers and improve scientific conclusions. Beswick et al designed a web-based multi-institutional registry for patients with sinonasal malignancies, a webbased, secure database to prospectively collect data in cases diagnosed with sinonasal malignancies [57]. This could be an incitement for further research of similar portals, especially in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Beswick et al. designed a web-based multi-institutional registry for patients with sinonasal malignancies, a web-based, secure database to prospectively collect data in cases diagnosed with sinonasal malignancies [ 57 ]. This could be an incitement for further research of similar portals, especially in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, immunologic/targeted therapy based on patients' genetic changes has been gradually applied to patients with mucosal melanoma, and our study also confirmed that the application of immunologic/targeted therapy had a beneficial impact on prognosis. Relevant studies have shown that the phenotypic changes related to MMHN include C-Kit, NRAS, and GNAQ [ 21 23 ], which are the targets of some targeted drugs, including vemurafenib, imatinib, and nilotinib [ 24 ]. Tumor-mediated immune tolerance is a focus at present.…”
Section: Discussionmentioning
confidence: 99%